2020
DOI: 10.1007/s10461-020-02808-2
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of Long-Acting Injectable Cabotegravir (CAB LA) in HIV-Uninfected Individuals: HPTN 077

Abstract: Long-acting injectable PrEP could offer an alternative to daily oral PrEP, improve adherence and protection, if found acceptable, safe and effective. HPTN 077 evaluated injectable cabotegravir safety, tolerability and pharmacokinetics among HIV-uninfected males and females in sequentially-enrolled cohorts of two dosing strategies. We compared acceptability of product attributes, prevention preferences and future interest in injectable PrEP (FIIP) by region, sex-at-birth, arm and cohort and used multivariable a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 34 publications
3
43
0
Order By: Relevance
“…It is noteworthy that participants' attitudes towards product attributes, including receiving two injectionsone in each buttock every two-months, was a stronger predictor of future interest in use than were their experiences with pain and other side effects. These findings are similar to acceptability data recently presented from a phase 2 trial of Cabotegravir LA (CAB LA) injectable (HPTN 077) [30] and a qualitative sub-study of ECLAIR, a phase 2 trial of CAB LA in MSM, which found overall high levels of acceptability, despite frequent but variable experiences of pain [31]. As additional long-acting PrEP modalities like implants and antibodies move through clinical trial research [32], there is an opportunity to further assess how participants understand and experience product features and the relative trade-offs they would consider in choosing and using a PrEP product.…”
Section: Discussionsupporting
confidence: 87%
“…It is noteworthy that participants' attitudes towards product attributes, including receiving two injectionsone in each buttock every two-months, was a stronger predictor of future interest in use than were their experiences with pain and other side effects. These findings are similar to acceptability data recently presented from a phase 2 trial of Cabotegravir LA (CAB LA) injectable (HPTN 077) [30] and a qualitative sub-study of ECLAIR, a phase 2 trial of CAB LA in MSM, which found overall high levels of acceptability, despite frequent but variable experiences of pain [31]. As additional long-acting PrEP modalities like implants and antibodies move through clinical trial research [32], there is an opportunity to further assess how participants understand and experience product features and the relative trade-offs they would consider in choosing and using a PrEP product.…”
Section: Discussionsupporting
confidence: 87%
“…As effective PrEP approaches (eg, pills, vaginal rings, 22 , 23 injectables, 24 etc) become licensed and scaled up and are increasingly accessible and acceptable, these biomedical tools will become part of the standard of prevention at the community level and in clinical trials. For trials, it could become increasingly challenging to convincingly show effectiveness of new biomedical HIV prevention technologies (eg, new PrEP drugs and HIV vaccines), if the expected rate of HIV infections will be small because of effective prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies, mostly done in adult women have suggested that delivery in a long-lasting injection would be a good target for drug development [15][16][17][18]. However, given the distinct developmental, physical and social differences between adult women and female adolescents [19], it is essential to explore how the mode of delivery of an HIV prevention option impacts acceptability and use in the adolescent population.…”
mentioning
confidence: 99%